What's in a bank of noon? Emily Dickinson and the bird in the garden. Issue 7 (10th November 2017) - Thomières, Daniel
ABSTRACT: One of the reasons why we read Emily Dickinson is because practically every one of her poems raises philosophical problems. In order to discover the scope of these problems, it seems essential to pay attention to the way the poet experiments with language. This essay starts from a study of the poem 'A Bird came down the Walk –' (J. 328 F. 359) in which she attempts to compare definitions of the self. The poem develops its own specific logic which is founded partially on metaphor, but mainly on hypallage and negation. The essay will try to assess the implications of Dickinson's linguistic, psychological and ontological experimentation.